Social Problems in the Novel "Sang Penakluk Angin" by Novanka Raja: A Sociology of Literature Review - Ernawati, Dwi; Sasongko, Sempu Dwi; Sardjono; Kurniawan, David Rindu (Asa Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
"Sang Penakluk Angin" by Novanka Raja is a novel that explores the struggles of Trimo's impoverished family and the social issues they encounter. The novel portrays the hardship faced by Trimo's family, with his father working as a goose feather washer and his mother selling cakes to make ends meet. Poverty, crime, and environmental problems are at the forefront of the story. Trimo's parents cannot afford his education, resulting in him dropping out of school in fifth grade and lacking knowledge. However, Trimo remains determined to succeed and pursues a career as a shuttlecock manager, undergoing job training. Throughout the novel, Trimo experiences crime, such as being hit by a bicycle ridden by his trouble-making friend Agung and being chased by a drunken motorcyclist. Environmental issues arise from the scattering of goose feathers used for shuttlecocks in Trimo's village. Overall, "The Wind Conqueror" presents important social aspects, emphasizing human values, wisdom, and lessons encouraging societal improvement and personal growth.